The importance of 5S implementation to the government sector at Pejabat Daerah Dan Tanah Pekan / Amani Khairunnisa Abu Hassan - Abu Hassan, Amani Khairunnisa (Faculty of Business And Management, 2013)
The study investigated the importance of 5S implementation to the government sector in Malaysia. This study contained independent variables with the impact of 5S implementation towards government staffs at the assigned place. This paper examined how these factors influenced productivity, quality and performance of the staff. The research had been carried out in Pejabat Daerah dan Tanah Pekan, Pahang (PDT). It used simple random sampling technique to collect all the data. The questionnaires were familiar to most people. Just as there was better and more delegated face to face when distributed the questionnaires. The finding showed 5S gave good impacts to the government staffs.